2011
DOI: 10.1111/j.1582-4934.2009.00958.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-kinase interacts with the glucocorticoid receptor upon TLR2 activation

Abstract: Airway inflammation is a common condition where glucocorticoids (GC) are a well-established therapy. It has been demonstrated that GC stimulate components of innate immunity. Specifically, GC up-regulate TLR2 expression and activation upon inflammatory stimuli; however, little is known about the signalling involved in this process. To determine the mechanism by which dexamethasone modulates TLR2-induced cytokine production this signalling pathway was monitored in a lung epithelial cell line exposed to the TLR2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 45 publications
1
18
1
Order By: Relevance
“…In many cell types, GRs profoundly induce MKP-1 expression, thus attenuating the activation of MAPKs. To address the mechanism by which GRs induce MKP-1, a very recent study has indicated that GRs directly interact with PI3K to impede the phosphorylation of AKT (58). Consistently, our data also indicate that treatment of cells with DEX attenuates the activation of PI3K/Akt by LPS.…”
Section: Discussionsupporting
confidence: 77%
“…In many cell types, GRs profoundly induce MKP-1 expression, thus attenuating the activation of MAPKs. To address the mechanism by which GRs induce MKP-1, a very recent study has indicated that GRs directly interact with PI3K to impede the phosphorylation of AKT (58). Consistently, our data also indicate that treatment of cells with DEX attenuates the activation of PI3K/Akt by LPS.…”
Section: Discussionsupporting
confidence: 77%
“…In this case, GCs exert non-genomic action to regulate protein metabolism by antagonizing insulin/IGF-1 responses. The interaction between GR and Pik3r1 proteins has been reported in other cell types (Arancibia et al, 2011; Hafezi-Moghadam et al, 2002; Leis et al, 2004). Identifying GR mutants that do not interact with Pik3r1 or Pik3r1 mutants which do not associate with GR will help dissect the mechanism of GC-regulated protein metabolism.…”
Section: The Regulation Of Protein Metabolism By Glucocorticoidsmentioning
confidence: 63%
“…PI3K physically interacts with the glucocorticoid receptor (GR) through two consensus YxxM binding motifs within the GR. 21 In human fibroblasts, DXM protects cells from apoptosis via activation of PKB/Akt. 22 DXM may enhance Akt activation by low doses of EH, thus playing a synergistic role in the expression of IL-10 while remaining a strong inhibitor of proinflammatory cytokine production.…”
Section: Discussionmentioning
confidence: 99%